Practical management of polyposis syndromes. Issue 4 (30th March 2019) - Patel, Roshani; Hyer, Warren
Abstract : Hereditary bowel tumours are usually part of a distinct syndrome which require management of both intestinal and extra-intestinal disease. Polyposis syndromes include: Familial adenomatous polyposis, MUTYH-associated polyposis, Serrated polyposis syndrome, Peutz-Jeghers syndrome, Juvenile polyposis syndrome and PTEN-hamartomatous syndromes. Of all colorectal cancers (CRC), 5%–10% will be due to an underlying hereditary CRC syndrome. Diagnosis and management of polyposis syndromes is constantly evolving as new scientific and technological advancements are made with respect to identifying causative genes and increased sophistication of endoscopic therapy to treat polyps. This, in addition to data yielded from meticulous record-keeping by polyposis registries has helped to guide management in what are otherwise relatively rare conditions. These data help guide clinical management of patients and their 'at-risk' relatives. Diagnosis is both genetic where possible but clinical recognition is key in the absence of an identifiable causative gene. Furthermore, some syndromes can overlap which can additionally complicate diagnosis. The principle goals of polyposis management are first to manage and treat the presenting patient and then to identify 'at-risk' patients, through screening and predictive genetic testing, endoscopic surveillance to allow therapy and guide surgical prophylaxis. Due to the complexity of diagnosis and management, patients and their families should be referred to a genetics centre or a polyposis registry where dedicated management can take place.